A RESEARCH CONDUCTED IN A DEVELOPING NATION STUDIED THE SATISFACTION LEVELS BETWEEN STUDENTS AND TEACHERS AT A PUBLIC UNIVERSITY. - Watts, Monika; Bhalla, G.S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education is one of the significant sources of income in the global market; India stands as the third largest producer of education systems for student enrollment after China and the United States. This research is aimed at evaluating and comparing the opinions of the students and teachers in the region following the various attributes deemed central in Guru Nanak Dev University, Amritsar. This study uses a quantitative research approach; the data collection technique employed is the survey. Feedbacks were received from the students and teachers studying and teaching on the main campus of GNDU and other regional centres at Amritsar, Jalandhar and Gurdaspur. The data collection system used was random and snowball sampling techniques to guarantee a diverse sample population. Of the 411 participants, 202 were students, 209 were teachers, and all completed structured questionnaires. The self-compiled survey intends to provide a comparative study of the level of satisfaction of students and teachers concerning the university’s various campuses to identify areas that require more attention in the University. Cultivating from this knowledge and field findings, the study can help determine the opportunities and issues in the context of GNDU’s educational system. It is the hope that the eight recommendations generated from the study can support policy change and institutional transformation, which will, in return, improve the tutoring quality, the quality and productivity of the faculty, as well as the learning quality of the students. Also, this research points out the developments that have taken place in India’s higher education sector and the antecedents linked to satisfaction in academic communities located in regional settings. Consequently, this study emphasises the need for structured assessment procedures for the enhancement of institutional efficiency and student achievement.